Umetnostna dediščina vitezov Klarwillov iz dvorca Podsmreka pri Višnji Gori - Košak, Tina (Acta historiae artis Slovenica, 2023)
The article analyses two late 18th century cabinet genre paintings kept in Podsmreka manor near Višnja Gora until the end of WWII and now in a private collection in Ljubljana. Based on the coat-of-arms on the wax seal and other labels on the back of the paintings, it can be confirmed that they originate from the collection of Isidor Ritter von Klarwill (1842–1898) in Vienna, part of which was transferred to Podsmreka in then Kingdom of Yugoslavia by Isidor’s grand-son Peter Klarwill. Based on archival sources, the article sheds light on the hitherto unknown circumstances of the transfer of a part of the Klarwill collection to Podsmreka in 1935, the sale of the Podsmreka manor to Anton Verovšek in 1939, and the fate of the manor’s furnishings and art collection after the end of WWII. Upon the sale of the castle to the state in 1948, several items were transferred from the manor to state museum collections. Their Viennese provenance has been traced and confirmed for the first time in this paper.
Keywords: art collections; castle furnishings; Dunaj (Avstrija); genre painting; Klarwill (rodbina); migracije; migration; new nobility; novo plemstvo; oprema gradov; Podsmreka (Slovenia); provenance; provenienca; umetnostne zbirke; Vienna (Austria); žanrsko slikarstvo